Analisis Hasil Belajar dalam Pembelajaran Jarak Jauh pada Materi Konsep Redoks - Rahmawati, Ulvi; Abdullah, Abdullah; Linda, Roza (Universitas Negeri Semarang, 2023)
The outbreak of the corona virus has caused many deaths and has an impact on activities such as education. Schools throughout Indonesia are closed, so the learning process is carried out online. There are various differences in the face-to-face and online learning process, because many things happen from the learning process. The purpose of this study was to determine student learning outcomes, student responses and the relationship between responses and learning outcomes of class X science students at SMA Negeri 1 Bengkalis on redox concept material using the Zoom application. This study uses a descriptive analysis method with a quantitative approach. The sample in this study was 120 students. Data collection techniques were carried out through test questions, student questionnaires and teacher interviews. The results showed that student learning outcomes were classified as poor with a percentage of 55.83% of students who passed the KKM, student responses were quite good and there was a positive relationship between student responses and learning outcomes with a coefficient value of r = 0.697, which was in the strong category.